Odpowiedź:
3/7 - ( 2 i 1/2 *7/25 -2/10)= 3/7 - ( 5/2 *7/25 - 2/10 ) (skracamy 5 i 25 przez 5)=
= 3/7 - ( 1/2 *7/5- 2/10)= 3/7 - ( 7/10-2/10)= 3/7 - 5/10= 3/7 - 1/2=
= 6/14- 7/14= - 1/14
Szczegółowe wyjaśnienie:
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Odpowiedź:
3/7 - ( 2 i 1/2 *7/25 -2/10)= 3/7 - ( 5/2 *7/25 - 2/10 ) (skracamy 5 i 25 przez 5)=
= 3/7 - ( 1/2 *7/5- 2/10)= 3/7 - ( 7/10-2/10)= 3/7 - 5/10= 3/7 - 1/2=
= 6/14- 7/14= - 1/14
Szczegółowe wyjaśnienie: